2007
DOI: 10.1007/s10549-007-9671-z
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory breast cancer: PET/CT, MRI, mammography, and sonography findings

Abstract: MRI was the most accurate imaging technique in detecting a primary BPL in IBC patients. Sonography can be useful in diagnosing regional nodal disease. PET/CT provides additional information on distant metastasis, and it should be considered in the initial staging of IBC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
133
6
19

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(166 citation statements)
references
References 22 publications
8
133
6
19
Order By: Relevance
“…MRI is highly sensitive for depicting primary breast parenchymal lesions and global skin abnormalities that may help diagnose inflammatory breast cancer. Lesions that were either heterogeneous or inhomogeneous, consisting of a reticular or dendritic internal enhancement with a washout or plateau kinetic curve, were commonly noted [26][27][28][29]. This is different from our findings in non-puerperal mastitis.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…MRI is highly sensitive for depicting primary breast parenchymal lesions and global skin abnormalities that may help diagnose inflammatory breast cancer. Lesions that were either heterogeneous or inhomogeneous, consisting of a reticular or dendritic internal enhancement with a washout or plateau kinetic curve, were commonly noted [26][27][28][29]. This is different from our findings in non-puerperal mastitis.…”
Section: Discussioncontrasting
confidence: 99%
“…Clinically, inflammatory breast cancer is characterised by the rapid onset of swelling and enlargement of the breast, the characteristic "peau d'orange" (orange peel) skin appearance and quick progression to nodules and ulcerations. This type of breast cancer is usually poorly differentiated in histology from infiltrating ductal carcinoma, which often has distant metastases at the time of diagnosis [8,26]. These aforementioned manifestations in non-puerperal mastitis are slight or rare [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is common clinical practice in patients with breast cancer to carry out ultrasound of the axilla together with fine needle aspiration cytology of any suspicious axillary nodes that are identified (or palpable) prior to patients undergoing SNB [10]. Similarly MRI [11,32], CT [33,34], mammography [7,11] and other non-PET radionuclides (MIBI) [25] have all been suggested as useful in the staging of the axilla. It would not be the aim to perform a complete review of all modalities at this stage, since an extensive number of studies have not been carried out in all modalities.…”
Section: Introductionmentioning
confidence: 99%
“…For the initial staging work-up, many conventional imaging modalities, such as X-ray mammography, MR mammography, chest plain radiography, bone scintigraphy, and breast, axillary and liver ultrasonography, have been widely utilized. In recent years, several groups have evaluated the clinical role of FDG-PET/CT for pretreatment evaluation of breast cancer in comparison with conventional imaging tools [18,39,[43][44][45][46][47][48][49][50][51][52][53][54] (Table 2). These studies revealed that FDG-PET/CT is generally helpful, but particularly valuable for detection of extra-axillary (infraclavicular, supraclavicular and internal mammary) nodal metastasis and occult distant metastasis relative to conventional modalities, especially in patients with inflammatory breast cancer [43,46,47] and stage II-III disease [18, Fig.…”
Section: Initial Stagingmentioning
confidence: 99%